2019
DOI: 10.1142/s0219581x18500266
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polylactide/Carbon Nanopowder Filament using Melt Extrusion and Filament Characterization for 3D Printing

Abstract: In this study, less expensive mesoporous nano carbon (NC) infused in polylactide (PLA) thermoplastic filaments were fabricated to improve the electrical properties and maintaining sufficient strength for 3D printing. Solution blending was used for PLA-NC nanocomposite fabrication and melt extrusion was employed to make cylindrical filaments. Mechanical and electrical properties of 1–20[Formula: see text]wt.% of NC-filaments were investigated and significant improvement of conductivity (3.76[Formula: see text]S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…CNTs play a special role in the mechanisms of stabilized heat release by ensuring the required levels of percolation of the conductive phase in the polymer matrix. [20] However, in many research articles [21][22][23] contradictory results are reported regarding the dependence of the percolation threshold on the CNTs aspect ratio. According to the excluded volume analysis, [21] the percolation threshold of suspension-containing carbon structures should decrease with an increase in their aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs play a special role in the mechanisms of stabilized heat release by ensuring the required levels of percolation of the conductive phase in the polymer matrix. [20] However, in many research articles [21][22][23] contradictory results are reported regarding the dependence of the percolation threshold on the CNTs aspect ratio. According to the excluded volume analysis, [21] the percolation threshold of suspension-containing carbon structures should decrease with an increase in their aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…All popular materials intended for FDM printing are also available as filled or reinforced filaments. Most often, they are glass or carbon fibers [ 16 , 17 , 18 ], although there are also commercial materials based on nanoadditives such as carbon nanotubes or graphene [ 19 , 20 , 21 ]. Unfortunately, due to the characteristics of the printing process, the content of these additives rarely exceeds 20%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of a new conductive lament is not a simple task, since an appropriate compromise between conductivity (to reach a minimal percolation threshold), printability, 1 homogeneity and exibility should be achieved. Moreover, this production requires an extruder machine for the conversion of the polymeric blend into a lament shape and the optimization of all steps (e.g., ratio among conductive particles, polymer and solvent to generate the composite powder/pellet and melting temperature and stirring rate of the extruder 24 ) is typically a time-consuming and expensive process. 26 Another alternative and less explored approach for the fabrication of sensors based on FDM additive manufacturing consists of the coating of insulating 3D-printed plastic surfaces with conductive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming for cheaper and “ready-to-use” filaments, few research groups have been developing bespoke filaments with higher carbon contents than the commercial ones. 3,23–25 For example, Foster et al 25 developed a composite filament of nanographite and polylactic acid (NG–PLA), in which the percentage of NG was varied in the range of 1 to 40 wt%. From this investigation, the optimized material presented 25 wt% of NG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation